2015
DOI: 10.11118/actaun201563010087
|View full text |Cite
|
Sign up to set email alerts
|

Use of ABA Treatment for the Activation of Drought Protective Mechanisms in Barley Under Non-stress Conditions

Abstract: ) at the early stage of the plant development. We used RIA method, instantaneous water use effi ciency (WUE), the discrimination of 13 C (Δ 13 C) and the expression levels of Dhn4 gene. The increase of ABA concentration in leaves a er exogenous ABA application was detected in all tested genotypes; however, the lowest amount was found in the most tolerant genotype. Increased level of the instantaneous WUE a er ABA treatment was found in all genotypes. The Δ 13 C in ABA treated plants decreased, however, relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Sivamani et al [80] confirmed an improvement of biomass and WUE in transgenic barley plants expressing HVA1 gene under drought conditions. Furthermore, Melišová et al [33] suggested that elevated expression of the HvDhn4 gene, which is also a Y n SK n -type dehydrin and similar to PpDhn2, was associated with the high WUE observed in a drought-tolerant variety of barley at 12 h after ABA treatment. Moreover, DREB TFs improved tolerance to abiotic stress in transgenic plants by regulation of genes involved in abiotic stress responses, so DREB TFs could increase WUE under water deficit conditions [81].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sivamani et al [80] confirmed an improvement of biomass and WUE in transgenic barley plants expressing HVA1 gene under drought conditions. Furthermore, Melišová et al [33] suggested that elevated expression of the HvDhn4 gene, which is also a Y n SK n -type dehydrin and similar to PpDhn2, was associated with the high WUE observed in a drought-tolerant variety of barley at 12 h after ABA treatment. Moreover, DREB TFs improved tolerance to abiotic stress in transgenic plants by regulation of genes involved in abiotic stress responses, so DREB TFs could increase WUE under water deficit conditions [81].…”
Section: Discussionmentioning
confidence: 99%
“…Carbon isotope discrimination (∆ 13 C) analysis is suggested as an appropriate indicator of long-term WUE at the leaf level [28,32]. The basis of this indirect method has been extensively studied [32][33][34] and suggests a negative correlation between WUE and ∆ 13 C. Furthermore, the relationship between ∆ 13 C and ash content has been studied in cereals [35,36], apple [37] and peach [38] in order to improve phenotyping and breeding for WUE. The association among these three parameters (WUE, ∆ 13 C and leaf ash content) is based on the passive transport of minerals via the xylem and their accumulation in growing and transpiring tissues.…”
Section: Introductionmentioning
confidence: 99%